Pengaruh Keterampilan Mengajar Guru dan Motivasi Belajar Siswa Terhadap Hasil Belajar Ekonomi dalam Pembelajaran Online - Gumanti, Dessyta; Respita, Reni; Teza, Serli Diovani (Lembaga Intelektual Muda (LIM) Maluku, 2023)
This research was carried out with the aim of finding out the influence of teacher teaching skills and student learning motivation on economic learning outcomes in online learning. The research was conducted at SMAN 1 Solok with a population of 432, then samples were drawn using proportional random sampling technique, obtaining a sample of 123 online learning students. This research uses a causal survey method. Research data was collected using research instruments in the form of questionnaires with a Likert scale and also students' UAS scores for learning outcome variables which were processed and analyzed using path analysis techniques. Data distribution is carried out using Google Form. The results of hypothesis testing showed that teachers' teaching skills have a significant effect on students' learning motivation in economics subjects in online learning at SMAN 1 Solok, Teachers' teaching skills have a significant effect on economics learning outcomes in online learning at SMAN 1 Solok, Teachers' teaching skills have a significant effect on economics learning outcomes. in online learning at SMAN 1 Solok which is mediated by learning motivation